Sleep loss disrupts the neural signature of successful learning. (25th April 2022) - Guttesen, Anna á V; Gaskell, M Gareth; Madden, Emily V; Appleby, Gabrielle; Cross, Zachariah R; Cairney, Scott A
Abstract: Sleep supports memory consolidation as well as next-day learning. The influential "Active Systems" account of offline consolidation suggests that sleep-associated memory processing paves the way for new learning, but empirical evidence in support of this idea is scarce. Using a within-subjects ( n  = 30), crossover design, we assessed behavioral and electrophysiological indices of episodic encoding after a night of sleep or total sleep deprivation in healthy adults (aged 18–25 years) and investigated whether behavioral performance was predicted by the overnight consolidation of episodic associations from the previous day. Sleep supported memory consolidation and next-day learning as compared to sleep deprivation. However, the magnitude of this sleep-associated consolidation benefit did not significantly predict the ability to form novel memories after sleep. Interestingly, sleep deprivation prompted a qualitative change in the neural signature of encoding: Whereas 12–20 Hz beta desynchronization—an established marker of successful encoding—was observed after sleep, sleep deprivation disrupted beta desynchrony during successful learning. Taken together, these findings suggest that effective learning depends on sleep but not necessarily on sleep-associated consolidation.